Belt and road in the new geo-political competition: China, the United States, Europe and Korea - Duyeon Kim (OrdnungsPolitisches Portal (OPO), 2021)
China under Xi Jinping is seeking to reshape international rules, norms, and institutions to gain political and economic influence under the guise of providing global public goods for mutual gains. Meanwhile, democratic and like-minded countries will need to compete in some areas and cooperate in other areas with China-a feat that is far easier said than done. The United States, Europe, Korea, and Asia must engage and compete with China on their terms, based on mutual respect and understanding without compromising values such as democracy, rule of law, and human rights as well as best practices including fair and open trade and reciprocity. These are certainly challenging tasks whose playbook and manual need to be written along the way. The United States, Europe, and South Korea must navigate unchartered territory, which China seeks to create in its image. They must identify ways to not only defend the rulesbased international order but prevent their respective economic interests from colliding with their shared interests, values, and purposes.
Keywords: 330; Belt and Road Initiative; United States; Europe; South Korea; Quad